WHY DO HIGHER-EDUCATION INSTITUTIONS PURSUE ONLINE EDUCATION? - Schiffman, Stephen; Vignare, Karen; Geith, Christine (Online Learning, 2007)
Using a unique item included for the first time in the Sloan Consortium’s 2006 national survey of online learning, the authors analyze the reasons why higher-education institutions engage in online learning. Nine reasons are explored from contributing to extension efforts to returning a surplus. Eight of the nine reasons are found to vary in importance depending on the type of institution. Significant differences were found for associate-level institutions, for-profit institutions and large-enrollment institutions. The authors examine the findings for access and quality themes.